Efeitos da estimulação transcraniana por corrente contínua e estimulação periférica na atividade elétrica do músculo tibial anterior e equilíbrio de indivíduos hemiparéticos – estudo clínico, controlado, randomizado e duplo cego - Fruhauf, Aline Marina Alves (2018)
The occurrence of motor control of the ankle after stroke, can significantly interfere in activities of daily living, especially in the balance operations. Apart from this, treatments that make lower extremity function become important. Objectives: Primary outcome: To analyze the electrical activity of the anterior tibial muscle (TA) and postural control of hemiparetic individuals as a result of stroke, after Transcranial Direct Current Stimulation (tDCS) associated with Peripheral Electrical Stimulation (PES); Secondary outcome: to evaluate functional mobility after treatment involving tDCS and PES. Methods: Thirty-six hemiparetic subjects diagnosed with chronic stroke, 59 ± 10 years, randomized into three treatment groups: 1) active PES associated with sham tDCS (PESa /tDCSs); 2) active PES associated with active tDCS (PESa/tDCSa) and PES sham associated with active tDCS (PESs/ ETCCa). Active tDCS and sham were applied in bilateral assembly (anode on motor cortex, injured hemisphere, cathode on uninjured motor cortex), 2mA; sham tDCS remained on for 20 seconds. PES was performed on paretic TA, 50 hz. Sessions lasting 30 minutes, five times a week, for 2 weeks, totaling 10 sessions. Evaluation: electric motor activity of the paretic TA muscle by the mean root mean square (RMS), during three maximal voluntary isometric contractions (CVM) and median frequency (MDF) (3 repetitions of 5 consecutive isotonic contractions) by means of electromyography; equilibrium was evaluated by the Mini-Balance Evaluation System (Mini-BESTest) and functional mobility by the Timed Up Go test. The evaluations were collected in three moments, pre, post 10 and follow-up 30 days of the interventions. Emg: there was no significant difference in RMS for any of the groups after 10 days of treatment and 30 days follow-up. The MDF measure decreased significantly (p <0.05) after 10 days of treatment and 30-day follow-up in all groups except the 30-day follow-up of the PESa/tDCSs group, in which a non-significant increase (p> 0.05) of the MDF in relation to the baseline condition; (p = 0.001) and PESs/tDCSa (p = 0.005) and after 30 days of PESa/tDCSa follow-up (p = 0.00) were significantly lower after 10 days of treatment for PESa /tDCSa and PESs/ETCCa (p = 0.001) compared to the PESa/tDCSp group. Equilibrium: balance improved significantly (p = 0.00) and clinically important (improvement of > that 3 points) in the PESa/tDCSa group for 10 days of treatment and 30-day follow-up; there was no significant difference (p> 0.05) between groups. In functional mobility there weren´t statistical differences in the results for either group. Conclusion: For the electrical activity of the TA muscle, the central stimulation with tDCS didn´t potentiate the effects of the PES, on the contrary, it led to a reduction of its activity. The same results were not observed for the postural control, since the association of the techniques provided a clinical improvement of this variable. There weren´t changes in the functional mobility.